On one Hidden Quote in V. F. Odoyevsky’s Story La Sylphide: An Attempt at Commentary - Kondiurina, Anna (Literatūra, 2025)
The article is an interpretation of Vladimir Odoyevsky’s story La Sylphide (1837), which consists of two qualitatively different parts: a real and a conceptual commentary. The first is devoted to identifying the hidden quotation, translating it, establishing the source (opera Tancredi by Gioachino Rossini). This part also provides factual information necessary to understand the complex of contents behind the reference and allowing one to understand its function in the overall concept of the work. In the second part, the subject of consideration is the plot of the story and its imagery, which has a rich philosophical and iconographic tradition (primarily, Neoplatonism and alchemical symbolism); through them, the problems of the work and V. Odoyevsky’s philosophical views, are revealed.
Keywords: opera; Rossini; Tancredi; alchemy; nature